Human age estimation based on pulp volume of canines for chronological age estimation: Preliminary research - Hidayat, Septian Rahmat; Oscandar, Fahmi; Malinda, Yuti; Sasmita, Inne Suherna; Dardjan, Murnisari; Murniati, Nani; Lita, Yurika Ambar (Padjadjaran Journal of Dentistry, 2018)
Introduction: Age estimation has an important role in the process of human identification and needs to be performed in an efficient, fast, and accurate ways. Age estimation based on the pulp cavity volume of canines was referring to the theory stated that the apposition of secondary dentine during human life could be determined as an age indicator. This study was aimed to estimate the human age based on the pulp volume of canines for chronological estimation. Methods: Forty-one canine teeth from Cone Beam Computed Tomography (CBCT) 3D image sample from Dental Hospital of the Faculty of Dentistry Universitas Padjadjaran segmented into dental pulp and enamel were prepared for measurement of pulp volume using the ITK SNAP volumetric software. Descriptive analysis of pulp volume and regression equations were generated from regression analysis of pulp volume and tested for age estimation. Result: Dentine thickness was found to be increased from adolescence age range until adulthood age range. Logarithmic regression between pulp volume was statistically significant (p < 0,001). The coefficient of determination (R2) was 0.753 with a standard deviation of 8.421. Mathematics model for estimating age was: Age = 79.523 – (18.194 x ln(Pulp Volume)). The pulp cavity and dentine thickness were decreasing along the age. The same equation was also used in the same sample. There were several differences between chronological age and estimated age approximately 8.4 years following the regression result of R2 (75.3%). The rest of the sample (24.7%) have a big difference, and this could be affected by modifying variables such as occlusal force and human error measurement procedures. Conclusion: The human age can be estimated by the pulp volume of canines.Keywords: Age estimation, pulp volume, canine, ITK-SNAP, CBCT.